A Case Study of Collective Promising Practices using ICT in EVS at Primary/ Elementary Teaching - Gepala, Gajendra (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Environmental Studies (EVS) provides an insight into our culture, human behavior towards nature, science, Mathematics, English and ICTs. EVS hence needs to be taught in relation with other subjects like the aforesaid and not been seen as a singular lone subject. Despite its significance, teaching EVS has been found to be challenging because of employing traditional modes of teaching. The purpose of this paper is to compare achievement and investigate levels of perception among the students.